The dynamics of an online community of practice involving teachers and researchers - Marques, Margarida Morais (2015)
In the literature, communities of practice (CoPs) are recognised as having potential to promote teachers’ professional development. However, the study of the dynamics of CoPs with teachers and researchers, and their impact on teachers’ professional development, is still scarce. Contributing to fill this gap, this paper presents a single case study of the dynamics of a Portuguese online CoP, created during the research project IPEC. The messages posted by the group’s members in online fora (the most used communication tool) and descriptive statistics of the use of the project’s platform are presented and discussed. The analysis shows different levels of participation among the members over two school years. The group’s dynamic fits an adaptation of Wenger et al.’s model of CoP development stages. Finally, this analysis allowed the presentation of suggestions concerning teachers’ involvement in CoPs and their professional development.